DEVELOPING DIMENSIONS OF INTERNAL AUDIT QUALITY TO EMPLOYEES AN EXPLORATORY STUDY IN GOVERNMENT BANKS. - Shaymaa Qasim Thamer; Sanaa Rashed Mohaisen (Scholar Express Journals, 2022)
This study aims to know the improvement of audit quality by conducting for employees in government institutions, where a questionnaire was distributed to 60 samples, and logistic regression was used to achieve the objectives of the study and test its hypotheses; the study relied on primary and secondary data
Keywords: Quality; Internal Audit